Comparing ARIA‐E severity scales and effects of treatment management thresholds. (20th December 2022) - Klein, Gregory; Bracoud, Luc; Purcell, Derk; Barakos, Jerome; Fiebach, Jochen B.; Scelsi, Marzia A.; Delmar, Paul; Lyons, Marco; Wojtowicz, Jakub; Bullain, Szofia; Barkhof, Frederik; Fontoura, Paulo; et al.
Abstract: Background: Vasogenic edema and sulcal effusions detected with Magnetic Resonance Imaging (MRI), known as Amyloid‐Related Imaging Abnormalities‐Edema (ARIA‐E), are manageable side effects of anti‐amyloid immunotherapies. Periodic MRI scans with severity assessment of ARIA‐E are used in clinical trials or to guide practice with these therapies. Several scales with varying complexity measure radiological ARIA‐E severity to guide dosing. The ongoing GRADUATE studies use the 60‐point Barkhof Grand Total Scale (BGTS) 1, continuing treatment for asymptomatic ARIA‐E ≤ 3, and temporarily suspending dosing for BGTS > 3. Other studies have used Simple ARIA‐E Severity Scales 2 (SAESS‐3, SAESS‐5), continuing treatment for asymptomatic SAESS‐3 ≤ 1, but temporarily suspending dose for SAESS‐3 > 1 3 . We previously reported good correlation between BGTS, SAESS‐3, and SAESS‐5 by a single reader. Here we report correlations among these scales scored by multiple readers and assess the impact of these various scores on ARIA management. Methods: T2‐FLAIR MRI scans were selected from a representative set of incident ARIA‐E cases (70 with previously detected ARIA‐E, 5 without ARIA‐E from original BGTS assessment) in the SCarlet RoAD (NCT01224106) and Marguerite RoAD (NCT02051608) Phase III studies. Three experienced neuroradiologists scored ARIA‐E severity using the 3 scales from pairs of baseline/follow‐up scans, blinded to prior read results. Median results of the 3 readers were computed for further analysis. Result: Inter‐reader agreement for all 3 scales was high (ICC=0.866 [0.811, 0.908], 0.888 [0.841, 0.924], and 0.858 [0.776, 0.910] for the SAESS‐3, SAESS‐5, and BGTS scales respectively). Spearman's rank correlation with BGTS scale was 0.88 for the SAESS‐3 scale and 0.90 for SAESS‐5. Median interquartile range (IQR) BGTS scores for the two simplified scales are shown in Figure 1. Best agreement for the SAESS‐3 > 1 treatment management threshold was achieved with BGTS > 3, with an accuracy of 93.3% (Figure 2). Conclusions: SAESS‐3 and SAESS‐5, which may be more suitable for routine clinical practice, are well correlated to the BGTS scale. Treatment management based on the SAESS‐3 > 1 threshold shows high agreement with the BGTS > 3 threshold. 1. Barkhof et al., 2013; AJNR 34:8. 2. Bracoud et al., 2017; AAIC. P1‐047. 3. ADUHELM (aducanumab‐avwa) FDA PI.